Prevalence of Diabetes and Its Associated Factors Among the Adult Tribal Population in Tamilnadu, India - Kalaivanan R; Palanivel Sundaram; Logaraj M; Anantharaman VV; Nancy Leon (Medsci Publications, 2024)
Background: Diabetes is increasing at alarming rate among Indians especially South Indians with prevalence of diabetes mellitus varying in populations of different regions. There are very limited data available among the tribals. A cross‑sectional study was conducted to estimate the prevalence of diabetes mellitus and its associated factors in an adult tribal population. Methodology: A total of 425 peoples were selected using multi-stage random sampling techniques. A modified STEP-wise questionnaire was used and detailed interview was conducted with the participants aged above 30 years. Random blood sugar and Body mass index (BMI) were estimated for all the participants. Chi-square and Adjusted Odds-ratio was used to study the strength of association. Results: Prevalence of diabetes was 7.8% (33) among the study participants and 92.2% (392) of them were non diabetic. Among diabetic 21.2% (7) were newly diagnosed, 33.3% (11) of them had diabetes between 1-5years, 21.2% (7) have diabetes between 5-10 years and 24.3% (8) of them had diabetes more than 10years. Increasing Age, Education, Physical-inactivity and Obesity showed a strong association with diabetes. Conclusions: The prevalence of diabetes and the burden of lifestyle risk factors for diabetes have been observed to be 7.8% among tribal populations in this study setting. Effective strategies to prevent this have to be devised.